2009
DOI: 10.1007/s12349-009-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

A nationally representative survey of hospital malnutrition: the Italian PIMAI (Project: Iatrogenic MAlnutrition in Italy) study

Abstract: *See the end of the text for the complete list of affiliations Overall prevalence of malnutrition was 30.7%, with higher rates in the northern macroarea (36.7%) than in central (28.0%), southern (26.9%) and island (16.7%) ones (p < 0.0001). This discrepancy appeared to be mainly related to the prevalence of overweight/obesity. By a multivariate model, malnutrition was significantly lower in males (p < 0.05) and surgical wards (p < 0.002), associated with geography (p < 0.05) and consistently higher in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…In recent years, a number of works have reported an increasing incidence of obesity in the general population, but data on the prevalence of obesity and overweight in the gastroenterological population have been limited. The average prevalence of overweightobesity in our study was 22.7%; this rate of obesity was lower than those reported in a hospital setting in previous Italian [28][29][30] reports but was higher than the Italian general population rate, especially in outpatients. We also found that approximately 10% of the obese and overweight hospitalized patients were undernourished and that the risk of malnutrition was present in more than one-third of the obese and overweight gastroenterological patients, with rates that reached 80% in > 65-year-old obese inpatients.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…In recent years, a number of works have reported an increasing incidence of obesity in the general population, but data on the prevalence of obesity and overweight in the gastroenterological population have been limited. The average prevalence of overweightobesity in our study was 22.7%; this rate of obesity was lower than those reported in a hospital setting in previous Italian [28][29][30] reports but was higher than the Italian general population rate, especially in outpatients. We also found that approximately 10% of the obese and overweight hospitalized patients were undernourished and that the risk of malnutrition was present in more than one-third of the obese and overweight gastroenterological patients, with rates that reached 80% in > 65-year-old obese inpatients.…”
Section: Discussioncontrasting
confidence: 84%
“…In our population, the prevalence of undernutrition was similar to those reported in other European [8] and Italian studies [28] but differed from other studies [9,29,30,50] because of both (1) the different tools used to evaluate malnutrition; and (2) the diverse stages of disease. In this study, we reported for the first time (1) the rate of undernutrition in gastroenterology outpatients; and (2) the correlation of undernutrition with hospital admission.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Accordingly, an economical projection of our data in a single non-university hospital (for example, Bolzano Hospital; 30 204 patients/year) suggests that disease-related malnutrition (reported prevalence: 30%) (Lucchin et al, 2009b) is responsible for an increase in healthcare costs of about 2 000 000 h per year, whereas the treatment (mean cost of 9-day nutrition support: 410 h), at least in patients presenting with overt malnutrition (prevalence 12%), can result in a money saving of 800 000-1 000 000 h per year (mean cost of 1-day stay: 603 h). It is worth mentioning that this evaluation does not take into account the additional indirect costs deriving from the possibly overlapping nutrition-related complications, such as infections or pressure ulcers.…”
Section: Discussionmentioning
confidence: 90%
“…Nutritional risk was diagnosed by the Nutritional Risk Screening 2002 tool (Lucchin et al, 2009a) and disease-related malnutrition by analytical criteria (Table 1) related to food intake and both anthropometric and biochemical parameters (Lucchin et al, 2009b). We evaluated the standards of nutritional care on the basis of: adherence to the study protocol (completeness of data collected) by the nutrition teams; physical and dietetic assessments were performed directly by the nutrition team that was responsible of suggesting to nurses the prescription of biochemical analyses (to be included among those prescribed for the following day).…”
Section: Methodsmentioning
confidence: 99%